Modulation of Theta-Band Local Field Potential Oscillations Across Brain Networks With Central Thalamic Deep Brain Stimulation to Enhance Spatial Working Memory - Chang, Ching-Wen; Lo, Yu-Chun; Lin, Sheng-Huang; Yang, Shih-Hung; Lin, Hui-Ching; Lin, Ting-Chun; Li, Ssu-Ju; Hsieh, Christine Chin-jung; Ro, Vina; Chung, Yueh-Jung; Chang, Yun-Chi; Lee, Chi-Wei; et al. (Frontiers in Neuroscience, 2019)
Deep brain stimulation (DBS) is a well-established technique for the treatment of movement and psychiatric disorders through the modulation of neural oscillatory activity and synaptic plasticity. The central thalamus (CT) has been indicated as a potential target for stimulation to enhance memory. However, the mechanisms underlying local field potential (LFP) oscillations and memory enhancement by CT-DBS remain unknown. In this study, we used CT-DBS to investigate the mechanisms underlying the changes in oscillatory communication between the CT and hippocampus, both of which are involved in spatial working memory. LFPs were recorded from microelectrode array implanted in the CT, dentate gyrus, cornu ammonis region 1, and cornu ammonis region 3. Functional connectivity (FC) strength was assessed by LFP–LFP coherence calculations for these brain regions. In addition, a T-maze behavioral task using a rat model was performed to assess the performance of spatial working memory. In DBS group, our results revealed that theta oscillations significantly increased in the CT and hippocampus compared with that in sham controls. As indicated by coherence, the FC between the CT and hippocampus significantly increased in the theta band after CT-DBS. Moreover, Western blotting showed that the protein expressions of the dopamine D1 and α4-nicotinic acetylcholine receptors were enhanced, whereas that of the dopamine D2 receptor decreased in the DBS group. In conclusion, the use of CT-DBS resulted in elevated theta oscillations, increased FC between the CT and hippocampus, and altered synaptic plasticity in the hippocampus, suggesting that CT-DBS is an effective approach for improving spatial working memory.